The Relationship Between Academic Stress And Self-Regulation in Learning on Academic Procrastination among Students at State Junior High Schools in Jakarta - Eka Sari; Happy Karlina Marjo; Eka Wahyuni (Universitas PGRI Yogyakarta, 2026)
Academic achievement is an essential indicator in education, yet it is often hindered by academic procrastination, defined as the tendency of students to delay completing tasks. Academic stress can influence procrastination, which refers to psychological pressure arising from learning demands, and self-regulation, the ability to manage emotions, behavior, and learning strategies. This study examines the relationship between academic stress and self-regulation with academic procrastination among junior high school students in Jakarta. The population consisted of 706 students from State Junior High School A (428 students) and State Junior High School B (278 students). Using Slovin’s formula with a 5% significance level, a sample of 371 students was obtained. Three measurement scales were employed to assess each variable. The results revealed a significant negative relationship between academic stress and self-regulation with procrastination. Pearson correlation coefficients were -0.632 (academic stress) and -0.430 (self-regulation), with p = 0.000 (p < 0.01). These findings highlight the importance of collaboration among students, counselors, and parents in time management and emotion regulation to foster a supportive learning environment and reduce procrastination. Keywords: academic stress, self-regulation, procrastination